The nature and rates of failed, rare, or obscured core-collapse supernovae and nuclear transients - Reynolds, Thomas Michael (fi=Turun yliopisto|en=University of Turku|, 2021)
In this thesis, two major types of astrophysical phenomena are discussed: corecollapse supernovae and transient events associated with supermassive black holes in the nuclei of galaxies. The physical processes and observable features associated with these events are described. Three articles included in the thesis concern core-collapse supernovae and their progenitors. The remaining two consider nuclear transients associated with accretion onto a supermassive black hole. The results have implications for a variety of fields, such as late stages of stellar evolution, corecollapse supernovae and their rates, and tidal disruption of stars by supermassive black holes. An archival search in Hubble Space Telescope data for vanishing massive stars is presented in Paper I. These can be associated with a core-collapse that fails to produce a bright supernova. We present a candidate failed supernova and discuss the implications of the discovery for the expected rate of these events. Paper II presents a study of an exceptional core-collapse supernova, SN 2016gsd. The unusual characteristics of this object are connected to the presence of circumstellar material around the progenitor star. The implications for the mass-loss experienced by the star are considered. A search for supernovae in luminous infrared galaxies is presented in Paper III. It is shown that the method of using near-infrared adaptive optics allows for discovery of supernovae close to galactic nuclei, and the implications of the new discoveries for the supernova rate in luminous infrared galaxies are considered. Paper IV describes a nuclear transient, AT 2017gbl, discovered in a luminous infrared galaxy. The properties of this event and the host galaxy are analysed through multi-wavelength observations. A stellar tidal disruption event is considered as the most likely explanation for the transient, and the implications of that conclusion are considered. Paper V presents an archival infrared search for similar nuclear transients in a sample of luminous infrared galaxies. New discoveries are described, the transient rate is derived, and the implications for the origin of such transients are discussed.